If you would like to simplify the following expression <span>(28x - 7y) + (32x + 52y), you can do this using the following steps:
</span>(28x - 7y) + (32x + 52y) = <span>28x - 7y + 32x + 52y = 28x + 32x - 7y + 52y = 60x + 45y
</span>
The correct result would be B. <span>60x + 45y.</span>
Answer:
y=-4x-2 so c
Step-by-step explanation:
the slope is always gonna be the number that is attached to the x
A. The function is bing translated down 5 units
b. The function is being stretched vertically stretched by 2 units
c. He function is being translated 5 units to the right
d. The functions being flipped and vertically stretched by 3 units
Answer:
a=7
Step-by-step explanation:
24^2+a^2=25^2
576+a^2=625
49=a^2
a=7